Self-training in unsedated transnasal EGD by endoscopists competent in standard peroral EGD: prospective assessment of the learning curve - Maffei, Massimo; Dumortier, Jérôme; Dumonceau, Jean-Marc (Gastrointestinal endoscopy, 2008)
Training programs in unsedated transnasal (UT) EGD are scarce. To prospectively assess the learning curve for unsupervised UT-EGD. Endoscopy service, without experience in UT-EGD. Consecutive patients referred for diagnostic EGD. UT-EGD was attempted in 140 study patients by 2 endoscopists who trained by themselves in UT-EGD (skilled endoscopist [n = 70]; a trainee having recently achieved competency in conventional EGD [n = 70]) and in 10 controls (endoscopist skilled in UT-EGD) by using a 4.9-mm-diameter videoendoscope. Technical success, sedation administered, patient tolerance acceptance, procedure duration for each decade of 10 consecutive patients investigated by the same endoscopist; intention-to-treat analysis. Both self-trained endoscopists fulfilled predefined criteria of competency in UT-EGD since the first attempts. They completed examinations of adequate quality with exclusive transnasal scope insertion (n = 139 [99.3%]), no sedation (n = 138 [98.6%]), and patient accepting repeat procedure (n = 135 [96.4%]) in proportions not significantly different from controls for all decades. Compared with a median procedure duration of 5.5 minutes (interquartile range [IQR] 5.0-8.5 minutes) in controls, procedures were significantly longer for all trainee's decades (eg, first decade 20.0 minutes [IQR 15.0-29.0 minutes], P < .001) but none for the skilled endoscopist. Overall discomfort, pain, gagging, and belching were not significantly different for study patients versus controls. Fifty-six of 69 study patients (81%) with a previous history of conventional EGD preferred UT-EGD. Generalizability to other small-caliber endoscopes. Endoscopists competent in conventional EGD may obtain excellent results with UT-EGD (except for procedure duration) beginning with their first attempts, even without supervision or structured training.